2000
DOI: 10.1016/s0012-365x(99)00132-6
|View full text |Cite
|
Sign up to set email alerts
|

Equational characterizations of Boolean function classes

Abstract: Several noteworthy classes of Boolean functions can be characterized by algebraic identities (e.g. the class of positive functions consists of all functions f satisfying the identity f(x) ∨ f(y) ∨ f(x ∨ y) = f(x ∨ y)). We give algebraic identities for several of the most frequently analyzed classes of Boolean functions (including Horn, quadratic, supermodular, and submodular functions) and proceed then to the general question of which classes of Boolean functions can be characterized by algebraic identities. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 16 publications
2
70
0
Order By: Relevance
“…This quasi-order can be described as follows: for f, g ∈ Ω, g ≤ f if g can be obtained from f by identification of variables, permutation of variables, and addition or deletion of dummy variables. As shown in [11], equational classes of Boolean functions coincide exactly with the initial segments ↓K = {g ∈ Ω : g ≤ f, for some f ∈ K} of this quasi-order, or equivalently, they correspond to antichains A of Boolean functions in the sense that they constitute sets of the form Ω \ ↑A. Moreover, those equational classes definable by finitely many equations correspond to finite antichains of Boolean functions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This quasi-order can be described as follows: for f, g ∈ Ω, g ≤ f if g can be obtained from f by identification of variables, permutation of variables, and addition or deletion of dummy variables. As shown in [11], equational classes of Boolean functions coincide exactly with the initial segments ↓K = {g ∈ Ω : g ≤ f, for some f ∈ K} of this quasi-order, or equivalently, they correspond to antichains A of Boolean functions in the sense that they constitute sets of the form Ω \ ↑A. Moreover, those equational classes definable by finitely many equations correspond to finite antichains of Boolean functions.…”
Section: Introductionmentioning
confidence: 86%
“…As it turned out, these two approaches have the same expressive power in the sense that they specify exactly the same classes (or properties) of Boolean functions. The characterization of these classes was first obtained by Ekin, Foldes, Hammer and Hellerstein [11] who showed that equational classes of Boolean functions can be completely described in terms of a quasi-ordering ≤ of the set Ω of all Boolean functions, called identification minor in [11,16], simple minor in [20,8,5,6], subfunction in [25], and simple variable substitution in [3]. This quasi-order can be described as follows: for f, g ∈ Ω, g ≤ f if g can be obtained from f by identification of variables, permutation of variables, and addition or deletion of dummy variables.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 3.1 (Ekin et al 2000) The recognition problem for the quadraticity property of a Boolean function given by a DNF is coNP-complete.…”
Section: Dualization Of Quadratic Boolean Functionsmentioning
confidence: 99%
“…Identification of variables together with permutation of variables and cylindrification induces a quasi-order on operations whose relevance has been made apparent by several authors [3,7,8,9,10,12,14]. In the case of Boolean functions, this quasi-order was studied in [4] where Theorem 2 was fundamental in deriving certain bounds on the essential arity of functions.…”
Section: Theoremmentioning
confidence: 99%